2019
DOI: 10.1186/s41936-019-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

AiP1, a protein from the coelomic fluid of sea star Astropecten indicus promotes wound healing and fibrinogenolysis in vitro

Abstract: Background: Marine animals are suspected to hold keys to counter several life-threatening diseases. Despite its vast biodiversity, the marine ecosystem is relatively unexplored for its therapeutic potential. This study was particularly aimed at finding a potent molecule against thrombosis from the coelomic fluid of a sea star (SCF). SCF is a reservoir of immunocytes, coelomocytes, cytokines, and other substances responsible for the exceptional regenerative potential and other bioactivities. Death due to thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
2
2
0
Order By: Relevance
“…The results hence indicated that the crude coelomic fluid from the sea star Astropecten indicus is a safe entrant for drug discovery. 14 However the results obtained from the present study for the in vitro analysis of hemolytic assay correlates with the finding that the compound isolated sea star Stellaster equestris even in a dose dependent manner were non-hemolytic and seems to be safe. The present study revealed that the purified sample did not show any cytotoxic effect on the exposed lymphocytes even in the dose dependant manner on comparison with the positive control.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results hence indicated that the crude coelomic fluid from the sea star Astropecten indicus is a safe entrant for drug discovery. 14 However the results obtained from the present study for the in vitro analysis of hemolytic assay correlates with the finding that the compound isolated sea star Stellaster equestris even in a dose dependent manner were non-hemolytic and seems to be safe. The present study revealed that the purified sample did not show any cytotoxic effect on the exposed lymphocytes even in the dose dependant manner on comparison with the positive control.…”
Section: Discussionsupporting
confidence: 86%
“…Previous study on the cell viability of the novel protein isolated from the coelomic fluid of sea stars Astropecten indicus reported to show increased cell viability in the time dependent manner indicating the protein molecule isolated from the coelomic fluid was not toxic. 14 Hence the present study correlates with the cell viability assay by trypan blue exclusion assay reporting to be non-toxic.…”
Section: Discussionsupporting
confidence: 54%
“…The preparation of the starfish coelomic fluid (CF) was performed by applying the same procedure described in the study of Baveja et al (2018Baveja et al ( , 2019; additional lengthy details were published by Abdel-Ghaffar and Youssef (2022). After centrifugation of the coelomic fluid, a pellet of cells was formed and prepared for microscopical examination.…”
Section: B Coelomic Fluid Extraction Procedures and Experimental Designmentioning
confidence: 99%
“…It is a benthic echinoderm that is typically found in the sediments of the intertidal and subtidal regions, where it feeds using infaunal molluscs, and represents a prototypic marine organism to study the effects of environmental pollution [169,170]. Recently, Baveja et al [171] isolated the AiP1 metalloproteinase from the coelomic fluid of A. indicus and demonstrated its fibrinolytic potential that is likely mediated by the von Willebrand factor (vWf)-like domain located in its central β sheet. Moreover, the ability of AiP1 to modulate the motile attitude of HaCaT keratinocytes and HEK293 embryonic kidney epithelial cells was checked through scratch wound healing assays demonstrating the additional AiP1-promoting effect on cell migration since vWf is known to sustain cell locomotory behavior.…”
Section: Echinodermatamentioning
confidence: 99%